Last chance tourism? Revealing true tourist motivations for visiting northernmost Alaska - Daniel Grafton; Amy Quandt; Vena Chu (Annals of Tourism Research Empirical Insights, 2025)
A prevailing narrative about last chance tourism, in which tourists visit threatened destinations, has made headlines in recent years as global climate change impacts became increasingly visible with landscapes and species facing the threat of disappearing. Tourist experiences in the Arctic and community views of climate change adaptation are underexamined in the existing literature. We interrogated the narrative of last chance tourism through archival research and qualitative content analysis of interviews from Utqiaçgvik, Alaska to uncover tourist motivations and residents' perceptions of tourists themselves. Results found two key findings: (1) last chance tourism played little role in motivating tourists; and (2) residents' perceptions of visitor motivations were notably different from tourists' own professed motivations.
Keywords: 330; Alaska; Climate change; Disappearing destinations; I\~nupiat; Last chance tourism; Motivations